Talimaya Gifts and Accessories Inc. a methods engineering study - Del Rosario, Geraldine; Galit, Jay-mie.; Talan, Mark Anthony (Diliman, Quezon City College of Engineering, 2005)
Talimaya Gifts and Accessories Corporation is a Philippine-based manufacturing company, which focuses on the creation of handbags using indigenous raw materials such as pandan, raffia, bancuan and abaca fibers. However, the existing intense competition among countries has lead to the decline in productivity of Talimaya and other manufacturing companies within the Philippines. Thus, with the objective of increasing overall productivity of Talimaya and improving its lay-out and working conditions, this Methods Engineering Study was performed. Subsequent Plant Visits were conducted and various observations and data gathering were undertaken. Analysis of data was then carried out using various Methods Engineering Tools. Data analysis showed that the major problems within Talimaya included its existing inefficient lay-out and its current working conditions. The lay-out of Talimaya was inefficient and hindered smooth material flow of materials while the current working conditions prohibited workers to carry out their jobs at optimal levels. Thus, alternatives addressing Talimaya's ineffective lay-out were implemented and other storage schemes were suggested to maximize floor space. Furthermore, alternatives addressing working conditions such as improved lighting and safety politics were also suggested to ensure worker satisfaction and overall productivity within the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Clothing trade -- Philippines; Systems analysis